Simulation of Alternative Plans for Community Based Goat Breeding Program in Arid, Semi-Arid and Mixed Production Systems in Ethiopia - Jembere, T.; Rischkowsky, Barbara A.; Dessie, Tadelle; Kebede, K.; Okeyo Mwai, Ally; Mirkena, T.; Haile, Aynalem (International Livestock Research Institute, 2021)
On station small ruminant researches in Ethiopia were ineffective due to various factors. As alternative, community based breeding program (CBBP) has emerged. In the current CBBPs, sire side selection only (SN1) is practiced. The objective of the present work was to compare SN1 by simulating alternative breeding scenarios for Abergelle (AB), Centeral Highland (CH) and Woyto-Guji (WG) goat breeds in Ethiopia. Three scenarios including selection on dam side (SN2) in addition to SN1, application of genomic selection (SN3) onto SN1 and use of sires from SN1 for mating in additional flocks (SN4) were simulated and compared with SN1 based on the predicted annual genetic gain (PAGG) and discounted profits. The breeding objective traits or selection criteria were six month weight (6mw, kg) for all breeds, average daily milk yield (ADM, kg) and survival to six month of age (SURV) for AB, litter size at birth (LSB) for CH and WG, litter size at weaning (LSW) for CH and kidding interval (KI, days) for WG. ZPLAN+ software was used for the simulation. The PAGG for 6mw (kg) ranged from 0.087 (SN4) to 0.25 (SN3) for AB where it ranged from 0.47 (SN4) to 0.97 (SN3) for ADM (kg) for same breed. PAGG in 6mw (kg) ranging from 0.13 (SN4) to 0.47 (SN3) and from 0.20 (SN4) to 0.31 (SN3) for CH Gonder and Ambo sites, respectively were simulated whereas this parameter ranged from 0.10 (SN4) to 0.27 (SN3) for WG. The alternative breeding scenarios to SN1 resulted in better PAGGs, especially for 6mw in three of the goat breeds and for ADM in AB. Based on the PAGGs and profitability, we recommend SN2 over SN1. However, SN4 could also be applied, compared to SN1, in view of suitability of addressing emerging demands.